Oxidized tyrosinase: A possible antigenic stimulus for non-segmental vitiligo autoantibodies. Issue 3 (September 2015) - Al-Shobaili, Hani A.; Rasheed, Zafar
Highlights This study demonstrates the role of oxidized tyrosinase in vitiligo autoimmunity. Modification in tyrosinase by ROS caused alteration in hydrophobic amino acids. ROS-induced epitopes on tyrosinase are strongly recognized by non-segmental Vt-IgG. Anti-ROS-tyrosinase-IgGs in vitiligo patients were increased with disease duration. Vitiligo patients' sera contain higher levels of carbonyl contents.